2020
DOI: 10.1108/yc-09-2019-1049
|View full text |Cite
|
Sign up to set email alerts
|

How can art museums develop new business opportunities? Exploring young visitors’ experience

Abstract: Purpose So far, most studies in cultural tourism have looked at visitors in relation to the experience itself. This study aims to bring a broader view on what constitutes the daily environment of younger visitors and how museums could use this knowledge to develop a service delivery that is more adapted to their needs without sacrificing the museums’ integrity and authenticity. As such, this research brings a unique and deeper analysis of young visitor behavior, in relation to arts and cultural practices that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Our review unveils that a limited number of papers apply or use a theory, with only six papers applying an existing theory. Batat (2020) explores art experiences among adolescents during their museum visits through the youth subculture theory developed by Hall and Jefferson (1976). Barbieri and Mahoney (2010) study consumption preferences within the context of life-performing art by applying the omnivorous–univorous consumption framework (Peterson, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Our review unveils that a limited number of papers apply or use a theory, with only six papers applying an existing theory. Batat (2020) explores art experiences among adolescents during their museum visits through the youth subculture theory developed by Hall and Jefferson (1976). Barbieri and Mahoney (2010) study consumption preferences within the context of life-performing art by applying the omnivorous–univorous consumption framework (Peterson, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, a symbolic brand value could change a brand into an iconic brand. Furthermore, young consumers are experienced and well-educated with classic marketing efforts (Batat, 2020). Maintaining and attracting young consumers need a fundamental change in response to enable young consumers with significant with them symbolic values (Esmaeilpour, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous homestay studies have focused on the perspectives of homestay operators and local communities (Fong et al , 2016), tourists’ perspectives, perceptions, perceived values and motivations for visiting rural homestays (Dey et al , 2020; Law and Lo, 2016), and young consumer’s behaviour towards cultural tourism, and the intention to visit future travel destination (Batat, 2020; Lončarić et al , 2019). Past literature has shown that demographic variables, including age, are vital for accurate market targeting in rural tourism (Batat, 2020; Chen et al , 2022; Yousaf et al , 2018), where young tourists aged between 15 and 30 contributed the most to the Malaysia tourism market (Kasim and Wickens, 2020). Studies focusing on community-based homestays among young adults in rural areas in Malaysia are limited, especially those focusing on the pandemic (Bao et al , 2018; Pasa, 2020).…”
Section: Introductionmentioning
confidence: 99%